EXTENT OF UTILIZATION OF ADVERTISING AS A MARKETING COMMUNICATION STRATEGY BY MANUFACTURING COMPANIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to improve and ensure effective marketability of products of manufacturingcompanies necessitated this study on the extent of utilization of advertising as amarketing communication strategy by manufacturing companies in Anambra State.One research question guided the study and two null hypotheses were tested.Descriptive survey research design was employed for the study. The populationconsisted of 298 executives (managers and owners) of registered manufacturingcompanies in Anambra State. The entire population was studied without samplingbecause the size was not too large.The instrument for data collection was aresearcher developed questionnaire titled “Marketing Communication StrategyQuestionnaire(MCSQ)”.The questionnaire was validated by three experts. Theinternal consistency of marketing communication strategy questionnaire (MCSQ)was established using Cronbach alpha and reliability coefficient value of 0.86 wasobtained. Mean and standard deviation were used to answer the research questionwhile t-test and ANOVA were used totestthe null hypotheses at 0.05 level ofsignificance. Findings of the study revealed that manufacturing companies inAnambra State utilized advertising to a moderate extent. It was recommendedamong others that business educators in tertiary institutions should be innovative intheir instructional delivery by exposing their students to all components ofmarketing communication strategies to enable them successfully operate their ownsmall and medium scale enterprises after graduation.